1996
DOI: 10.1099/0022-1317-77-3-443
|View full text |Cite
|
Sign up to set email alerts
|

til-1: a novel proviral insertion locus for Moloney murine leukaemia virus in lymphomas of CD2-myc transgenic mice

Abstract: Moloney murine leukaemia virus (MoMLV) markedly accelerates thymic lymphoma development in mice carrying a transgene in which the human c-myc gene is linked to the CD2 locus control region. To investigate the mechanism of synergy and identify the genes which collaborate with myc in these clonal tumours, we analysed the sites of MoMLV insertion. Analysis of known viral integration loci revealed only a small number of insertions at bmi-1, pim-1 and ahi-1. Further cloning and hybridization analysis revealed a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Our previous studies identi®ed the Cbfa1 gene as a frequent target for transcriptional activation by Moloney murine leukaemia virus in lymphomas of CD2-myc mice and showed that the over-expressed gene encodes multiple isoforms, the most abundant of which is G1 (Stewart et al, 1996(Stewart et al, , 1997. Moreover, we have found that over-expression of Cbfa1 in the thymus perturbs T-cell development, causing a pronounced skew towards CD8SP thymocytes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our previous studies identi®ed the Cbfa1 gene as a frequent target for transcriptional activation by Moloney murine leukaemia virus in lymphomas of CD2-myc mice and showed that the over-expressed gene encodes multiple isoforms, the most abundant of which is G1 (Stewart et al, 1996(Stewart et al, , 1997. Moreover, we have found that over-expression of Cbfa1 in the thymus perturbs T-cell development, causing a pronounced skew towards CD8SP thymocytes.…”
Section: Discussionmentioning
confidence: 84%
“…As we identi®ed the til-1/Cbfa1 gene as a potential myc-collaborating gene (Stewart et al, 1996(Stewart et al, , 1997 we assessed the e ect of crossing CD2-Cbfa1-G1 mice with CD2-myc transgenic animals. CD2-myc mice develop T-cell tumours, primarily involving the thymus, at an incidence of around 30% by 12 months of age depending on the genetic background (Stewart et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The CD2-MYC mice selectively express the c-MYC oncogene in T cells. Although uninfected mice develop tumors infrequently, murine leukemia virus infection at birth accelerates tumor onset: all infected mice succumb to thymic lymphomas by 80 days (Stewart et al, 1996). After screening the viral-induced thymic lymphomas, a proviral integration site was uncovered 30 kb upstream of the Runx3 distal P1 promoter.…”
Section: Insertional Mutagenesis Screen Implicates Runx3 In Tumor Devmentioning
confidence: 99%
“…Instead, we de®ned the Til1 locus as a common target in a signi®cant proportion of tumours and we have subsequently shown that these insertions activate transcription of the Runx2/Cbfa1/Aml3/Pebp2aA gene (hereafter Runx2) (Stewart et al, 1996(Stewart et al, , 1997. By a similar approach, Girard et al (1996) showed that Notch1 is the preferred target for viral acceleration/ activation in their MMTVd-Myc transgenic model.…”
Section: Introductionmentioning
confidence: 99%